Theory of Magnetization Plateaux in the Shastry-Sutherland Model - Dorier, J.; Schmidt, Kai Phillip; Mila, F. (Physical Review Letters, 2008)
Motivated by the remarkable properties of SrCu(2)(BO(3))(2) in a magnetic field, we use perturbative continuous unitary transformations to determine the magnetization plateaux of the Shastry-Sutherland model, unveiling an unexpected sequence of plateaux progressively appearing at 2/9, 1/6, 1/9, and 2/15 upon increasing the interdimer coupling. We predict that a 1/6 plateau should be present in SrCu(2)(BO(3))(2), even if residual interactions beyond the Shastry-Sutherland are strong enough to modify the other plateaux below 1/3. The method is extended to calculate the magnetization profile within the plateaux, leading to a local structure around triplons that agrees with NMR results on SrCu(2)(BO(3))(2).